Bilingual lexical disambiguation: the nature of the effects of lexical coactivation between languages - Areas da Luz Fontes, Ana Beatriz (2010)
The present study tested whether lexical disambiguation in sentence context is affected by cross-language lexical activation. In the dominant meaning shared condition, Spanish-English bilinguals read English sentences biasing the subordinate meaning of homonyms that were either cognates or non-cognates. Participants’ ability to reject follow-up target words related to the dominant meaning showed greatest inhibition when the homonym was a cognate and the dominant meaning was shared with Spanish. In the subordinate meaning shared condition, Spanish-English bilinguals read sentences biasing the dominant meaning of the homonyms and were instructed to accept target words related to any meaning of the homonym. In this case, cognate status of the homonym facilitated acceptance of targets related to the subordinate meaning when this was shared with Spanish. Findings are discussed in terms of expanding current models of lexical disambiguation to account for bilingual processing.